Unveiling of Commemorative Plaque (1950)
Harold O. Wilson, President McPhee, Charles Voorhis, and Assemblyman Ernest Geddes at the unveiling of the plaque commemorating the 1938 gift of the Voorhis ranch to Cal Poly.